(Re)descriptions of medical professional work: exploring accounting as a performative device within an emergency unit health-care context. Issue 2 (18th May 2020) - Fırtın, Cemil Eren; Karlsson, Tom S.
Abstract : Purpose: This article addresses issues of calculation and economization in contemporary public organizations. In particular, it investigates how choices of organizing emergency health-care have been affected by accounting as a performative device. Special attention has been paid to how accounting brings about performative consequences in shaping the medical profession and its context. Design/methodology/approach: The article employs qualitative research methods and draws its analysis on empirical data from in-depth interviews at an emergency health-care unit in Sweden. Findings: It is demonstrated how accounting, in the form of calculations of treatment time and number of patients, enables performative consequences for medical professional work. It is also demonstrated how the use of accounting engages (re)descriptions of practices and roles, creates accounts of patients, and helps to sustain such (re)descriptions. Accounting terms (such as efficiency and control) have been reframed into medical terminology (such as health-care quality and security), ensuring and retaining (re)described medical professional work in terms of practices and emerging roles. Originality/value: This article contributes to (1) the literature on accounting practices within health-care contexts by demonstrating a case where the accounting ideas and practices of medical professionals are coexistent and interwoven and (2) the increasing body of literature focusing on accountingization by showing how emerging calculative technologies carry performative power over medical professional work through formative (re)descriptions.